2019
DOI: 10.3390/genes10080614
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Animal Models Used in Acute Myeloid Leukemia Pathophysiology

Abstract: Acute myeloid leukemia (AML) is one of the most frequent, complex, and heterogeneous hematological malignancies. AML prognosis largely depends on acquired cytogenetic, epigenetic, and molecular abnormalities. Despite the improvement in understanding the biology of AML, survival rates remain quite low. Animal models offer a valuable tool to recapitulate different AML subtypes, and to assess the potential role of novel and known mutations in disease progression. This review provides a comprehensive and critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 251 publications
0
21
0
1
Order By: Relevance
“…Both, transgenic [ 49 ] and knock-in [ 78 ] mouse models expressing FLT3 ITD in the haematopoietic compartment revealed that FLT3 ITD mutations enhance survival and proliferation of lymphoid and myeloid progenitor cells and induced in particular a myeloproliferative syndrome [ 79 ], resembling chronic myelomonocytic leukaemia [ 78 ]. Thus, FLT3 ITD itself is not sufficient to induce AML in rodent and zebra fish models [ 80 ], but rather needs an initiating oncogenic event to fully drive leukemogenesis. Accordingly, in mouse models, FLT3 ITD was shown to cooperate with other oncogenic mutations found in patients to induce human AML-like syndromes.…”
Section: Flt3 In Leukaemiamentioning
confidence: 99%
See 2 more Smart Citations
“…Both, transgenic [ 49 ] and knock-in [ 78 ] mouse models expressing FLT3 ITD in the haematopoietic compartment revealed that FLT3 ITD mutations enhance survival and proliferation of lymphoid and myeloid progenitor cells and induced in particular a myeloproliferative syndrome [ 79 ], resembling chronic myelomonocytic leukaemia [ 78 ]. Thus, FLT3 ITD itself is not sufficient to induce AML in rodent and zebra fish models [ 80 ], but rather needs an initiating oncogenic event to fully drive leukemogenesis. Accordingly, in mouse models, FLT3 ITD was shown to cooperate with other oncogenic mutations found in patients to induce human AML-like syndromes.…”
Section: Flt3 In Leukaemiamentioning
confidence: 99%
“…After a period of latency, these mice develop AML with short life span and extra-medullary involvement. Fusion of the nucleopore protein NUP98 to the homeobox protein HOXD13 occurs in human myelodysplastic syndrome [ 80 ]. Transgenic expression of NUP98-HOXD13 was shown in a mouse model to cooperate with FLT3 ITD to induce AML with short latency and 100% penetrance [ 83 ].…”
Section: Flt3 In Leukaemiamentioning
confidence: 99%
See 1 more Smart Citation
“…The above-mentioned features, together with the fact that the development of the hematopoietic system has cellular bases and regulatory mechanisms very similar to those described in mammals, make zebrafish a unique model for the study of hematooncological diseases. This is well illustrated by examples of myeloproliferative neoplasms (MPN) [ 1 ] and acute myeloid leukemias (AML) [ 2 ]. A comprehensive summary of zebrafish as a model in tumor biology with a detailed presentation of various types of studied neoplasms and techniques is given in a review article by M. Hason and P. Bartunek [ 3 ].…”
mentioning
confidence: 99%
“…AML is a very common hematological neoplasia with a heterogeneous genetic basis, and suitable animal models are a key tool for the analysis of individual AML (sub)types. The authors also report the use of Drosophila as an invertebrate model to study the chromosomal translocation t (8:21) (q22; q22), which is very frequent in AML [ 2 ].…”
mentioning
confidence: 99%